2009
DOI: 10.3233/nre-2009-0475
|View full text |Cite
|
Sign up to set email alerts
|

FES-propelled cycling of SCI subjects with highly spastic leg musculature

Abstract: Background: The presence of spasms precludes the use of artificial electrical activation of the muscles to restore mobility. The prospect of using an electrical stimulus that produces motor activation without causing unwanted reflex activation in patients with high levels of spasticity is an appealing one. Objective: The purpose of the study was to determine the efficacy of modulated middle frequency alternating current (MFAC) muscle stimulation compared to the conventional method of standard low frequency rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…c and Table ), which ultimately led to large errors. This was unexpected because although it is not possible to predict spasticity , many works reported decreasing of spasticity in FES and cycling protocols with SCI and other neurologically impaired subjects, , even when these are highly spastic .…”
Section: Discussionmentioning
confidence: 96%
“…c and Table ), which ultimately led to large errors. This was unexpected because although it is not possible to predict spasticity , many works reported decreasing of spasticity in FES and cycling protocols with SCI and other neurologically impaired subjects, , even when these are highly spastic .…”
Section: Discussionmentioning
confidence: 96%
“…Several studies (13,37,38) have shown that FES cycling reduces spasticity-an effect that can be seen in daily practice, if the recommended stimulation schedule is followed faithfully. The schedule represents three times a week of 30-min FES cycling (7,13,39).…”
Section: Discussionmentioning
confidence: 99%
“…FES propelled cycling lead to reduced spasticity in SCI subjects who achieved smooth pedaling in different studies (Hoffman, 1986; Katz, 1991; Krause et al, 2008; Szecsi and Schiller, 2009). In a study by Rösche et al (1997) a motorized exercise-cycle was also used to treat spasticity in subjects who suffered predominantly from multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Physiotherapy, mechanical, and electrical equipments are usual methods prescribed for performing physical exercise in spinal cord injured patients, but they are time consuming and costly (Sköld et al, 2002; Duffell et al, 2008; Szecsi and Schiller, 2009). In recent years, new methods are introduced to help patients conduct physical exercises independently at home and this has been an evolution and a great progress.…”
Section: Introductionmentioning
confidence: 99%